The associations between VDR BsmI polymorphisms and risk of vitamin D deficiency, obesity and insulin resistance in adolescents residing in a tropical country - Rahmadhani, R.; Zaharan, N.L.; Mohamed, Zahurin; Moy, Foong Ming; Jalaludin, Muhammad Yazid (Public Library of Science, 2017)
Background: The vitamin D receptor (VDR) gene is expressed abundantly in different tissues; including adipocytes and pancreatic beta cells. The rs1544410 or BsmI single nucleotide polymorphism (SNP) in the intronic region of the VDR gene has been previously associated with vitamin D levels, obesity and insulin resistance. Aims: This study was aimed to examine the association between BsmI polymorphism and risk of vitamin D deficiency, obesity and insulin resistance in adolescents living in a tropical country. Methods: Thirteen-year-old adolescents were recruited via multistage sampling from twenty-three randomly selected schools across the city of Kuala Lumpur, Malaysia (n = 941). Anthropometric measurements were obtained. Obesity was defined as body mass index higher than the 95th percentile of the WHO chart. Levels of fasting serum vitamin D (25-hydroxyvitamin D (25(OH)D)), glucose and insulin were measured. HOMA-IR was calculated as an indicator for insulin resistance. Genotyping was performed using the Sequenom MassARRAY platform (n = 807). The associations between BsmI and vitamin D, anthropometric parameters and HOMA-IR were examined using analysis of covariance and logistic regression. Result: Those with AA genotype of BsmI had significantly lower levels of 25(OH)D (p = 0.001) compared to other genotypes. No significant differences was found across genotypes for obesity parameters. The AA genotype was associated with higher risk of vitamin D deficiency (p = 0.03) and insulin resistance (p = 0.03) compared to GG. The A allele was significantly associated with increased risk of vitamin D deficiency compared to G allele (adjusted odds ratio (OR) = 1.63 (95% Confidence Interval (CI) 1.03–2.59, p = 0.04). In those with concurrent vitamin D deficiency, having an A allele significantly increased their risk of having insulin resistance compared to G allele (adjusted OR = 2.66 (95% CI 1.36–5.19, p = 0.004). Conclusion: VDR BsmI polymorphism was significantly associated with vitamin D deficiency and insulin resistance, but not with obesity in this population.